The financial performance of Standard Chartered Bank / Azfarina Zulkffli - Zulkffli, Azfarina (Faculty of Business and Management, 2010)
This report has been done to study the financial performance of Standard Chartered Bank. For completion of this report, secondary data and other approaches such as common sizing, financial ratios and gap analysis has been use as a data collection. The data is taken from external sources such as journal, internet, and newspaper. Besides that, by using financial ratio analysis we can determine the profitability of the company, whether it is profitable or not. Other than that, we also can determine how liquid the assets of the company when there is a downturn economic situation. The finding of the ratio show company is not doing well in year 2008. This is because of the global economic crisis in year 2008 where it affects the business of the company, and at the end it gives a less return to the company. By doing this study, we can determine the strength and weaknesses of the company. In order to meet their customer’s needs and satisfaction, they should maintain and improve their services with developing several strategies. Hopefully, this report can give valuable information about the performance of the company to their customers, and other parties.